Hepatocyte nuclear factor 1 alpha (HNF1A) regulates transcription of O‐GlcNAc transferase in a negative feedback mechanism. Issue 10 (14th May 2019) - Zhang, Chuanhui; Xie, Fei; Li, Ling; Zhang, Cheng; Zhang, Yong; Ying, Wantao; Liu, Li; Yan, Xuli; Yin, Futao; Zhang, Lianwen
Abstract : O ‐GlcNAc transferase (OGT)‐catalyzed protein O‐GlcNAcylation is implicated in diverse cellular events. In the present study, we report the regulation of ogt transcription by the hepatocyte nuclear factor 1 homologue A (HNF1A) in HEK293T cells. We first identified a core ogt promoter (−150 to +200 bp) and confirmed its binding to the transcription factor HNF1A. We found that HNF1A regulates ogt transcription in a time‐dependent manner and that O‐GlcNAcylation of HNF1A represses ogt transcription. Electron‐transfer dissociation based tandem mass spectrometry analysis revealed 14 O ‐GlcNAc sites on HNF1A, six of which are predominantly modified, including Ser 303/304, Ser 471, Ser 560 and Thr 563/564 . We further found that loss of O‐GlcNAcylation at Ser 303/304 or Thr 563/564 significantly elevates ogt transcription. These findings highlight a negative feedback mechanism for ogt transcription, which partially explains the homeostasis of cellular O‐GlcNAcylation. Abstract :